Biomechanical effects of dental implant diameter, connection type, and bone density on microgap formation and fatigue failure: A finite element analysis. (March 2021) - Lee, Hyeonjong; Jo, Minhye; Noh, Gunwoo
Highlights: l Three-dimensional dental implant finite element models with vertical and oblique loadings l Influence of connection types, implant diameters, and bone densities on microgap formation and fatigue life l Tissue-level connection type-induced low microgap formation and high resistance to fatigue failure ABSTRACT: Background and Objective: Understanding fatigue failure and microgap formation in dental implants, abutments, and screws under various clinical circumstances is clinically meaningful. In this study, these aspects were evaluated based on implant diameter, connection type, and bone density. Methods: Twelve three-dimensional finite element models were constructed by combining two bone densities (low and high), two connection types (bone and tissue levels), and three implant diameters (3.5, 4.0, and 4.5 mm). Each model was composed of cortical and cancellous bone tissues, the nerve canal, and the implant complex. After the screw was preloaded, vertical (100 N) and oblique (200 N) loadings were applied. The relative displacements at the interfaces between implant, abutment, and screw were analyzed. The fatigue lives of the titanium alloy (Ti–6Al–4V) components were calculated through repetitive mastication simulations. Mann–Whitney U and Kruskal–Wallis one-way tests were performed on the 50 highest displacement values of each model. Results: At the implant/abutment interface, large microgaps were observed under oblique loading in the buccal direction. At the abutment/screw interface, microgap formation increased along the implant diameter under vertical loading but decreased under oblique loading (p < 0.001); the largest microgap formation occurred in the lingual direction. In all cases, the bone-level connection induced larger microgap formation than the tissue-level connections. Moreover, only the bone-level connection models showed fatigue failure, and the minimum fatigue life was observed for the implant diameter of 3.5 mm. Conclusions: Tissue-level implants possess biomechanical advantages compared to bone-level ones. Two-piece implants with diameters below 3.5 mm should be avoided in the posterior mandibular area.